"People Power": Social Planners and Conflicting Memories of the Australian Assistance Plan. (May 2019) - Collins, Carolyn; Oppenheimer, Melanie
Abstract : The Australian Assistance Plan (AAP), Gough Whitlam's controversial programme of social welfare reform in the 1970s, was promoted as a national experiment in "people power." But the outpouring of often highly critical evaluations during and immediately after its brief existence failed to take into account the experiences of the programme's grassroots workers. This article focuses on the oral history component of a wider history of the AAP, and on those employed to realise Whitlam's vision – the social planners – comparing their backgrounds, roles, expectations, and frequently conflicting experiences as they shaped, and were shaped by, this "bold but crazy" experiment.